Will central bank digital currency disintermediate banks? - Toni Marion Whited; Yufeng Wu; Kairong Xiao (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2023)
We estimate a dynamic banking model to quantify the impact of a central bank digital currency (CBDC) on the banking system. Our counterfactuals show that a one-dollar introduction of CBDC replaces bank deposits by around 80 cents on the margin. Bank lending falls by one-fourth of the drop in deposits because banks partially replace lost deposits with wholesale funding. This substitution raises banks' interest-rate risk exposure and lowers their resilience to negative equity shocks. If CBDC bears interest or is intermediated through banks, it captures a greater deposit market share, amplifying the impact on lending. The effect on lending is amplified for small banks, for which wholesale funding is more expensive.
Keywords: E51; E52; G21; G28; 330; central bank digital currency; banking competition; maturity mismatch; financial stability